(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Soybean, like other grain legumes, requires some essential nutrients to accomplish the dual purpose of fixing atmospheric nitrogen and high yielding. A screen house experiment was then setup to investigate the effect of N, P, K, Zn and Mo onnodulation and growth of soybean. Soils from six farmers’ fields in Kaya, northern Guinea savanna and seven fertilizercompounds were used in a factorial experiment laid out in completely randomized design. Data collected at 8 weeks afterplanting on biomass yields, nodulation variables, N2-fixation, mycorrhizal roots colonization, and N and P uptake wereanalyzed using SAS. Soils test revealed variation of soils’ chemical contents among farmers field, especially for P with51.7 mg kg-1in Soil 1 to 2.7 mg kg-1in Soil 4. Significant effects from soils and fertilizers were observed on biomass yield,nodulation and nutrient uptake. Nitrogen fixation potential of TGX 1448–2E, however, was not increased by soils orfertilizer treatments. Soil x fertilizer effects was significant on P-uptake, shoot and nodule dry weight. It was observed thatK application reduced shoot dry weight and P-uptake in soil 1. Owing to these results in response to fertilizer treatments,soybean fertilization should be recommended according to soil inherent fertility.